Low-gradient aortic valve stenosis: value and limitations of dobutamine stress testing. Issue 3 (18th April 2006) - Bermejo, J; Yotti, R
Abstract : Aortic valve stenosis has already reached endemic proportions in Western countries. As the prognosis of low-flow aortic valve stenosis under medical treatment is dismal, surgery is recommended in most patients. Preoperative dobutamine stress testing may help to assess surgical risk, but there is no strong scientific evidence to deny surgery based exclusively on the results of this test. The problems associated with clinical decision making in this condition are reviewed.